A Systematic Review of Agreement Between Perceived and Objective Neighborhood Environment Measures and Associations With Physical Activity Outcomes. (October 2017) - Orstad, Stephanie L.; McDonough, Meghan H.; Stapleton, Shauna; Altincekic, Ceren; Troped, Philip J.
A number of review studies document associations between the perceived and objectively measured neighborhood environment and physical activity. However, current evidence does not discern whether perceived or objective variables more consistently predict physical activity. A review is needed to examine the comparability of these variables and the consistency of their respective associations with the same physical activity outcome. We systematically searched three databases for studies that examined agreement between perceived and objective measures and/or associations between comparable variables and physical activity. We abstracted 85 relevant peer-reviewed studies published between 1990 and 2015, synthesized agreement coefficients, and compared these variables' associations with physical activity. Perceived neighborhood environment variables were significantly associated with physical activity ( p < .05) at slightly higher rates than objective neighborhood environment variables (20.1% and 13.7%). Comparably defined variables exhibited low agreement and only 8.2% were associated with the same outcome. The perceived neighborhood environment and objectively measured neighborhood environment are related but distinct constructs that account for unique variance in physical activity.